The influence rare earth ions doping on the photoluminescent properties of indium hydroxide - Motta, F. V.; Marques, A. P.A.; Paskocimas, C. A.; Bomio, M. R.D.; Souza, R. P.; Abreu, M. F.C. [UNESP]; Li, M. S.; Varela, J. A. [UNESP]; Longo, E. [UNESP] (My University, 2013)
Crystalline rare earth ions -doped indium hydroxide (In(OH)3:RE3+) nanostructures were prepared by a rapid and efficient Microwave-Assisted Hydrothermal (MAH) method. The influence of doping rare earth (RE) ions (Eu, Tb and Tm) on the luminescence of In(OH)3 was studied. Nanostructures were obtained at a low temperature. FE-SEM images confirm that these samples are composed of 3D nanostructures. XRD, optical diffuse reflectance and photoluminescence (PL) measurements were used to characterize the products. Emission spectra of RE-doped indium hydroxide samples under excitation (350.7 nm) presented broad band emission referent to the indium hydroxide (In(OH)3) matrix. Relative intensities of the RE3+ emissions increased as the concentration of this ion increased from 0, 1, 2, 4 and 8 mol %, of Eu3+, but the luminescence is drastically quenched for the In(OH)3 matrix. © 2013 by Nova Science Publishers, Inc. All rights reserved.
Keywords: Hydrothermal; Hydroxide; Indium; Microwave; Nanostructures